Eating behaviours, the frequency of consumption of selected food products, and selected elements of lifestyle among young dancers - Elżbieta Szczepańska; Barbara Janota; Marika Wlazło; Martyna Czapla (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Proper nutrition and balanced physical activity have a beneficial effect on the growth and development of young athletes, supporting their endurance and health, which is particularly important in the period of adolescence. Objective. Aim of this study was to assess eating behaviours, frequency of consumption of some food products and selected elements of lifestyle among young dancers, as well as to compare the age of the dancers and the assessed behavior. Material and methods. The study included 198 dancers aged 10-15 years. An originally developed questionnaire was used as a research tool. Results. The largest group of dancers (43%) spent on training up to 2 hours per week. The recommended 4-5 meals/day were consumed by 61.1% of dancers, with 87.4% of respondents having breakfast on a daily basis. The recommendations on the daily intake of several portions of fruit and vegetables were followed by 49% and 36.9% of dancers, respectively. It is observed, that the consumption rates of sweets increased, while the consumption rates of fruit decreased with dancers'age. The consumption rates of packed lunch and afternoon snack increased, whereas the consumption rates of dinner decreased with an increasing number of hours spent training. Conclusions. Eating behaviours and the frequency of consumption of food products by young dancers can be described as varied. Their diet is characterised by regular consumption of meals and a correct frequency of consumption of most food products, including high intake of fruit and vegetables, yoghurt and kefir, as well as low consumption of fast food products. The selected elements of dancers' lifestyle, such as sleep time and physical activity, are mostly correct.